A state of the art about use of WhatsApp as an educational resource - Bragiatto , Gabriel Aparecido; Bueno, Luzia (Seven Editora, 2023)
The purpose of this article is to present the results of the survey of scientific production on WhatsApp as a tool for pedagogical use. For this, the "State of the Art" methodology was used, which consists of a study of everything that was researched and built in the area, from the search for descriptors in a database. In the case of this research, the SciELO (Brasil Scientific Electronic Library Online) platform was selected. The descriptors "WhatsApp, mobile, m-learning, learning, education, teaching, literacy, literacy and academic literacy" were used. As for the results, the 17 articles were presented along with which level of education they were present and which areas are interdisciplinary with the research. Among the articles, their contributions to thinking about the use of WhatsApp in education were also presented, namely: the use of WhatsApp by the subjects before the research; their various positive perceptions; its use in teacher training, orality, language teaching and health; needs of the development of new technological competences.DOI:https://doi.org/10.56238/alookdevelopv1-044